Anne's house of dreams - Montgomery, L. M. (Lucy Maud), 1874-1942 (Mumbai : Wilco International, 2023)
Anne's own true love, Gilbert Blythe, is finally a doctor, and in the sunshine of the old orchard, among their dearest friends, they are about to speak their vows. Soon the happy couple will be bound for a new life together and their own dream house, on the misty purple shores of Four Winds Harbor. A new life means fresh problems to solve, fresh surprises. Anne and Gilbert will make new friends and meet their neighbors: Captain Jim, the lighthouse attendant, with his sad stories of the sea; Miss Cornelia Bryant, the lady who speaks from the heart$1 (Band speaks her mind; and the tragically beautiful Leslie Moore, into whose dark life Anne shines a brilliant light.s
Keywords: Marriage -- Fiction; Domestic fiction